Diseño de un detector de sonidos de motosierra con bajo consumo energético. - Villegas-Li, Andrey David (Instituto Tecnológico de Costa Rica, 2013)
With the objective to safeguard protected areas located in our national lands against the illegal hunting and logging, it is necessary to provide the institutions in charge the management and care of these conservation areas with detection mechanisms automated of sounds of gun_re and chainsaws. For this, some algorithms intended for the detection of periodicity are tested using the LabVIEW software suit. Periodicity is a sound characteristic common to internal combustion engines such as cars and chainsaws.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2013.
Keywords: Labview; Motosierra; Procesamiento digital de señales; Acústica; Sonido; Caza ilegal; Tala ilegal